2001
DOI: 10.1074/jbc.m102766200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitochondrial Carbamoyl-phosphate Synthetase 1 Activity by Active Site Fatty Acylation

Abstract: In addition to its role in reversible membrane localization of signal-transducing proteins, protein fatty acylation could play a role in the regulation of mitochondrial metabolism. Previous studies have shown that several acylated proteins exist in mitochondria isolated from COS-7 cells and rat liver. Here, a prominent fatty-acylated 165-kDa protein from rat liver mitochondria was identified as carbamoyl-phosphate synthetase 1 (CPS 1). Covalently attached palmitate was linked to CPS 1 via a thioester bond resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 50 publications
(57 reference statements)
6
55
0
Order By: Relevance
“…This resulted in an approximate 100 M circulating concentration of -alkynyl-palmitate. After 1 or 4 h postinjection, livers were excised and a homogenate was made as described in Corvi et al ( 23 ). Samples (5 mg) of postnuclear supernatant (1,000 g ) were solubilized in RIPA buffer and used in immunoprecipitation experiments with rat anti-pan-Ras 259 antibody as described above.…”
Section: In Vivo Labeling Of Ras Proteins With -Alkynyl-palmitate In mentioning
confidence: 99%
See 3 more Smart Citations
“…This resulted in an approximate 100 M circulating concentration of -alkynyl-palmitate. After 1 or 4 h postinjection, livers were excised and a homogenate was made as described in Corvi et al ( 23 ). Samples (5 mg) of postnuclear supernatant (1,000 g ) were solubilized in RIPA buffer and used in immunoprecipitation experiments with rat anti-pan-Ras 259 antibody as described above.…”
Section: In Vivo Labeling Of Ras Proteins With -Alkynyl-palmitate In mentioning
confidence: 99%
“…Crude mitochondrial fractions were obtained using differential centrifugation as described in Corvi et al ( 23 ). All buffers contained freshly added EDTA-free Complete protease inhibitor cocktail.…”
Section: Mitochondrial Isolation From Rat Primary Hepatocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…First, studies on palmitoylation in mitochondria isolated from COS-7 cells and rat liver found that the majority of fatty-acylated protein in the mitochondrial matrix was urea-specific CPS (26). Although this study did not determine the site of palmitoylation, the findings that reaction with palmitoyl-CoA inactivated CPS and that the inactivation was prevented by ATP inclusion or prior FSBA treatment are consistent with Cys-1327 and/or Cys-1337 as the site(s) of palmitoylation.…”
Section: Resultsmentioning
confidence: 99%